Analisis Keberlanjutan Pemanfaatan Energi Panas Bumi di Kawasan Pembangkit Listrik Tenaga Panas Bumi (PLTP) Ulumbu Nusa Tenggara Timur - Bonita, Dwi Putri; Wihadanto, Ake; Rusdiyanto, Edi (SENTRI: Jurnal Riset Ilmiah, 2025)
This study aims to analyze the sustainability of geothermal energy utilization at the Ulumbu Geothermal Power Plant (PLTP) in East Nusa Tenggara by focusing on five key dimensions: environmental, social, economic, technological, and institutional. The analysis was conducted using the Rapid Appraisal for Multidimension (Rap-MD) method with Multidimensional Scaling (MDS), validated through Monte Carlo simulation to ensure the robustness of the results. Primary data were collected through questionnaires and interviews, while secondary data were obtained from official documents and previous studies. The findings reveal that the sustainability status of PLTP Ulumbu is classified as “moderately sustainable,” with an aggregate index value of 58%. The environmental (60.80%) and social (60.60%) dimensions achieved the highest scores, followed by economic (59.41%), technological (57.24%), and institutional (52.00%) aspects, the latter being the weakest. Sensitive factors influencing sustainability include community education level, poverty rate, land-use conditions, waste treatment technology, and the role of local institutions. These results emphasize the importance of strengthening collaboration among government, PLN, and local communities to maximize geothermal energy benefits, support economic development, and preserve ecological balance. The study provides strategic insights for policymakers and stakeholders in formulating sustainable renewable energy development strategies in Indonesia.